ABSORBTION DRYING-EVAPORATIVE HEAT USING SYSMEMS FOR COLD PRODUCTION WITH THE USE OF ALTERNATIVE ENERGY SOURCES - Doroshenko A.V.; Hasan Sadi Ibraghim (Problems of the Regional Energetics, 2010)
Direct and indirect evaporative coolers with nozzles based on multi channel and multi layer polymeric structures are examined in the paper. Such coolers can be used in both independent and combined variants, as well as a part of solar drying-evaporative systems. Heat required for the regeneration of absorbent is provided with solar energy from flat solar collectors from polymeric materials.